2011
DOI: 10.1603/an09149
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation and Inheritance of Diapause Induction in Two Distinct Voltine Ecotypes of Ostrinia nubilalis (Lepidoptera: Crambidae)

Abstract: European corn borer, Ostrinia nubilalis (Hübner) (Lepidoptera: Crambidae), displays a larval diapause in response to short photoperiods and is adapted to a variety of local conditions throughout North America. Hence, the effective photoperiod inducing larval diapause will differ among geographic ecotypes. This study considers the inheritance of photoperiodic larval diapause induction by hybridization and backcrossing two latitudinally distinct ecotypes of the European corn borer collected between 41° N, 96° W … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 32 publications
(44 reference statements)
8
34
0
Order By: Relevance
“…The putative sex-linked inversion we document in Ostrinia appears consistent with the large-effect, multicomponent prediction of chromosomal rearrangement models of speciation. First, multiple 'speciation phenotypes' (Shaw and Mullen, 2011) in ECB have known sex-linked factors, including male pheromone response and diapause timing (McLeod, 1978;Dopman et al, 2004;Wanner et al, 2010;Ikten et al, 2011). Second, a recent study indicated that large isolation effect sizes are common between ECB strains (RI ⩾ 0.5 for 4 of 7 forms of isolation; Dopman et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The putative sex-linked inversion we document in Ostrinia appears consistent with the large-effect, multicomponent prediction of chromosomal rearrangement models of speciation. First, multiple 'speciation phenotypes' (Shaw and Mullen, 2011) in ECB have known sex-linked factors, including male pheromone response and diapause timing (McLeod, 1978;Dopman et al, 2004;Wanner et al, 2010;Ikten et al, 2011). Second, a recent study indicated that large isolation effect sizes are common between ECB strains (RI ⩾ 0.5 for 4 of 7 forms of isolation; Dopman et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It seems that the incidence of diapause may be determined predominantly by the paternal line in Lepidoptera. Such as, the European corn borer, O. nubilalis (Reed et al, 1981;Ikten et al, 2011), the Asian corn borer, O. furnacalis (Xia et al, 2012) and the comma butterfly, P. c-album (Söderlind and Nylin, 2011), in which diapause is determined in a large part by the male in their reciprocal crosses. In the reciprocal crosses of H. armigera, there was also a significant interaction between direction of cross and sex; the incidences of diapause in the N Â D progeny under short daylengths of 12 and 13 h at 20°C were significantly higher than those in the N Â D progeny ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Crosses made between geographic strains for most insect species show diapause characteristics of all F 1 hybrids that are intermediate between those of their parents, such as the knot-grass moth, Acronycta rumicis, the arctiid moth, Spilosoma menthastri, the cabbage butterfly, Pieris brassicae, the satin moth, Leucoma salicis (Danilevskii, 1965), the boll Weevil, Anthonomus grandis (McCoy et al, 1968), the flesh fly, Sarcophaga peregrina (Kurahashi and Ohtaki, 1977), the anise swallowtail, Papilio zelicaon (Sims, 1983), the face fly, Musca autumnalis (Kim et al, 1995), the cabbage beetle, Colaphellus bowringi (Kuang et al, 2011), the European corn borer, Ostrinia nubilalis (Ikten et al, 2011), the comma butterfly, Polygonia c-album (Söderlind and Nylin, 2011) and the Asian corn borer, Ostrinia furnacalis (Xia et al, 2012), indicating that the genetic control of the photoperiodic response is polygenic for these species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies indicate that the male plays a more important role in the determination of diapause in its progeny, for example, in several species of Lepido ptera (Ikten et al, 2011;Chen et al, 2012;Xia et al, 2012;Huang et al, 2013;Fu et al, 2015;Xiao et al, 2015;Pruisscher et al, 2017). In some other insects in other orders, however, females have the same (Paolucci et al, 2016) or an even stronger (Kuang et al, 2011;Chen et al, 2014;French et al, 2014) infl uence than males on diapause in their progeny.…”
Section: Discussionmentioning
confidence: 99%